2018
DOI: 10.31032/ijbpas/2018/7.5.4446
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF Nigella sativa, Zingiber officinale, Cinnamomum zeylanicum ON SERUM LIPID PROFILE, GLUCOSE, WEIGHT, AND KIDNEY FUNCTION TESTS IN THE ANIMAL MODEL OF STZ INDUCED DIABETES MELLITUS IN MALE RATS

Abstract: This study was conducted to observe the serum biochemical changes associated with Diabetes Mellitus, in the STZ induced Diabetic rats, treated with Nigella sativa, Cinnamon and ginger. The study was comprised of forty adult male wistar rats, divided into eight groups of five each. Group I Untreated rats, Group II Diabetic rats (Intra-venous injection of 60mg/kg dose of Streptozotocin), the positive control group. Group III Preventive Ginger.Group IV Preventive Cinnamon: Group V Preventive Nigella sativa. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The present study revealed that cinnamon has a significant hypoglycemic supplement in both protective and therapeutic groups. Similar results were reported previously by Muhammad & Sangi (2018) and recently by Sivapriya & John (2020) . Similar results were also obtained by Sahib, 2016 , Costello et al, 2016 who found that cinnamon as 1gm/day-controlled blood sugar in diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study revealed that cinnamon has a significant hypoglycemic supplement in both protective and therapeutic groups. Similar results were reported previously by Muhammad & Sangi (2018) and recently by Sivapriya & John (2020) . Similar results were also obtained by Sahib, 2016 , Costello et al, 2016 who found that cinnamon as 1gm/day-controlled blood sugar in diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, plasma glucose levels were considerably lower in both pre-and post-treatment groups who were given ginger water extract. Muhammad & Sangi (2018) reported that aqueous extract of ginger (500 mg/mL) results in an improvement of hyperglycemic status in diabetic rats. Elshater et al (2009) showed that ginger and its active ingredient; gingerol regulated glucose metabolism by decreasing glycogenolysis and gluconeogenesis with subsequent reductions in hepatic glucose production and blood glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations